Efficiency Costs of Myanmar's Multiple Exchange Rate Regime - Hori, Masahiro; Wong, Yu Ching (Washington, D.C. : International Monetary Fund, 2008)
Myanmar's multiple exchange rate system creates various economic distortions. This paper describes the exchange rate practices in Myanmar, develops a model of foreign exchange markets, and presents the efficiency costs imposed by quasi-fiscal operation under the current exchange rate regime. The results of our model-based analyses indicate that the equilibrium exchange rate under the unified market could be at around K 400-500 per U.S. dollar, and using the equilibrium exchange rate (instead of the official exchange rate) as the accounting rate increases trade openness to more than 20 percent from less than 1 percent measured by official statistics. The total efficiency loss caused by the current multiple exchange rate regime is estimated at about 14-17 percent of GDP in 2006/07.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet